Combining Aerial photogrammetry and Terrestrial lidar for reservoir analog modeling - Buckley, Simon J. (2010)
High-resolution aerial photography was captured covering a geological outcrop at Castle Creek, British Columbia, Canada. Here, for the purposes of hydrocarbon analog modeling, the outcrop was required to be accurately surveyed, so that key stratigraphic surfaces could be mapped in three dimensions. Because the outcrop strata were vertically orientated, these surfaces could be tracked over a wide area; however, to provide a true reconstruction of the geology, it was necessary to also model localized vertical cliffs providing a cross-section through the stratigraphy. Terrestrial lidar was utilized to cover these cliff sections which were poorly represented in the 2.5D aerial data. The integrated outcrop surface was textured with metric aerial and terrestrial imagery providing a photorealistic model that could be used for interpretation by geologists. This formed the basis for building a geocellular model of the geological volume, which was used to assist in the understanding of subsurface reservoirs where data are often limited. © 2010 American Society for Photogrammetry and Remote Sensing.